Cover Picture: Direct Synthesis of Highly Designable Hybrid Metal Hydroxide Nanosheets by Using Tripodal Ligands as One‐Size‐Fits‐All Modifiers (Chem. Eur. J. 21/2017). Issue 21 (20th February 2017) - Kuroda, Yoshiyuki; Koichi, Tatsuyuki; Muramatsu, Keisuke; Yamaguchi, Kazuya; Mizuno, Noritaka; Shimojima, Atsushi; Wada, Hiroaki; Kuroda, Kazuyuki
Abstract : A generalized synthetic method for organically modified metal hydroxide nanosheets using tripodal ligands as one‐size‐fits‐all modifiers is demonstrated. A variety of metal hydroxide nanosheets consisting of transition‐metal cations were prepared directly from solutions. The tripodal structure of the ligands provides adaptability to a wide range of structures and high stability to hydrolysis. This method allows the design of both inorganic framework and organic surface functional groups. More information can be found in the Full Paper by Y. Kuroda, K. Kuroda et al. onpage 5023 ff.